Big Data and Artificial Intelligence for Improving the Performance and Efficiency of Large-Scale Grid-Connected PV Power Plant - Amiri Ahmed Faris (University of M'Sila, 2024)
This thesis presents reliable methods for fault detection and diagnosis in Photovoltaic (PV) systems. The first method proposes a two step approach for developing a reliable PV model and constructed a fault detection procedure using Random Forest Classifiers (RFCs). The first step involves identifying the unknown parameters of the One Diode Model (ODM) using the Modified Grey Wolf Optimization (MGWO) algorithm and simulating the PV array t o extract maximum power point (MPP) coordinates. The second step involves developing two RFCs: one for fault detection and another for fault diagnosis. The second method uses the Sandia Array Performance Model (SAPM) for accurate photovoltaic system si mulation. Parameters are extracted with the Artificial Bee Colony (ABC) algorithm to optimize and reduce errors between measured and simulated data. Additionally, deep learning is employed by combining Convolutional Neural Networks (CNN) and Bidirectional Gated Recurrent Units (Bi GRU) to analyze dynamic system power outputs at the MPP for fault detection and diagnosis with high precision. The third work develops a predictive modeling method for PV generation using rigorous feature selection, outlier re moval, and hyperparameter tuning. The method is implemented in a MATLAB interface to predict key parameters and evaluate system performance. The efficiency of these methods is evaluated using real data from actual PV systems.
هذه الأطروحة تقدم حلو ا لً فعّالة وبسيطة للكشف عن الأعطال وتشخيصها في أنظمة الطاقة الكهروضوئية (PV). يتمحور العمل حول ثلاث طرق رئيسية : تعتمد الطريقة الأولى على نهج من خطوتين: الأولى تتضمن إنشاء نموذج دقيق للألواح الكهروضوئية باستخدام نموذج الصمام الثنائي الواحد (One-Diode Model) ، حيث يتم تحديد المعلمات غير المعروفة للنموذج باستخدام خوارزمية الذئب الرمادي المحسنة (Modified Grey Wolf) واستخراج إحداثيات نقطة الطاقة القصوى .(MPP) الثانية تتمثل في تطوير مصنّفين باستخدام خوارزميات الغابة العشوائية (Random Forest Classifiers) ، حيث يكون الأول مخص ا صا لتحديد الأعطال والثاني لتشخيص نوع العطل . الطريقة الثانية تعتمد على استخدام نموذج أداء المصفوفات الكهروضوئية للسانديا (SAPM) لمحاكاة سلوك الألواح الكهروضوئية بدقة. يتم استخراج المعلمات الخاصة بهذا النموذج باستخدام خوارزمية خلية النحل الًصطناعية (ABC) لتقليل الأخطاء بين البيانات الفعلية والنموذجية. كما تعتمد على التعلم العميق باستخدام مزيج من الشبكة العصبية الًلتفافية (CNN) ووحدة البوابة التكرارية ثنائية الًتجاه (Bi-GRU) لتحليل المخرجات الديناميكية للكشف عن الأعطال وتشخيصها بدقة . الطريقة الثالثة تهدف إلى نمذجة وتوقع إنتاج الطاقة الكهروضوئية وتحليل أداء النظام. تتضمن هذه الطريقة إزالة البيانات الشاذة، اختيار الميزات الأكثر تأثي ا را، وضبط المعلمات لتحسين أداء النماذج التنبؤية. تم تنفيذ هذه الطريقة داخل واجهة MATLAB لتسهيل استخدامها في التطبيقات الواقعية . تم تقييم فعالية هذه الطرق باستخدام بيانات حقيقية من أنظمة طاقة كهروضوئية، مما يثبت كفاءتها في تحسين أداء الأنظمة والكشف عن الأعطال بدقة وسرعة .
Keywords: faults; Random Forest Classifiers; Modified Grey Wolf Optimization; Convolutional Neural Network; Bidirectional Gated Recurrent Unit; deep learning.; Photovoltaic; الطاقة الشمسية، الأعطال، مصنفات الغابات العشوائية، خوارزمية الذئب الرمادي المحسنة، الشبكة العصبية الًلتفافية وحدة البوابة التكرارية ثنائية الًتجاه، التعلم العميق